Stranding and incidental catch of sea turtles in the coastal Tumbes, Peru - Rosales, Carlos A. (2010)
Strandings and incidental catches of four sea turtles species (Chelonia mydas, Lepidochelys olivacea, Dermochelys coriacea and Eretmochelys imbricata) were registered in Tumbes Region since August 2007 to August 2009. These registers (52.6% of strandings and 47.4% of incidental catches) occurred during all year; most frequently in Punta Picos (50.5%), Canoas (20.0%) and Baja de Punta Mero (14.7%). The most registered species were C. mydas (64.2%) and L. olivacea (30.5%); their sizes did not present significant differences between areas and climatic seasons. The higher percentage of C. mydas, L. olivacea and D. coriacea were considered sub-adults, including the only specimen of E. imbricata. The incidental catches were made with gillnets of different mesh sizes, but 8 inches mesh was most frequently. A high proportions of specimens were died with signs of drowning (22.2%) this was due to the prolonged time of soak time of gillnet (approximately 12 hours). No significant differences in CPUE were found between climatic seasons and no seasonal pattern was evident. Lesions in 14% of stranded specimens were caused possibly by human attacks or by collisions with fishing boats. 77.8% of incidental catch specimens were sacrificed for the commercialization of his meat, and sometimes of his shell, this shows the lack of awareness of conservation. These observations indicate that the coast of Tumbes is an important foraging area and development of sub-adult specimens of sea turtles; so it is recomend to develop monitoring, awareness and critical areas protection programs to foment the conservation of these organisms in the Eastern Pacific.